Distribución Espacial de Vectores de la Enfermedad de Chagas en el Estado de Guanajuato 1998-2000 - López Cárdenas, Jorge; González Bravo, Francisco Ernesto; Salazar Schettino, Paz María (Acta Universitaria, 2002)
This study has been perfomed in order to verify the existence and location of vectors of Chagas disease in the entities of Guanajuato state to limit the territories and risk areas. Determining the infection of Trypanosoma cruzi in the vectors, evaluates the risk to human population. This research has been conducted evaluating the information of the labeled triatominos obtained by the field personnel of the Secretaria de Salud del estado de Guanajuato, and classified by the Laboratorio Estatal de Salud del Estado de Guanajuato. The information was obtained from 1998 to 2000 in the entities where work brigades are located and the reported abscence of vectors probably is due the absence of search on them. The index of infestation was not performed due the different search intensity across the territory and the sample method. Just the location of every studied specie to the collecting area was established. Triatoma mexicana, T. barberi, T. longipennis, T. pallidipennis y T. dimidiata, was present in 162 places of 25 entities of the states; at heighs of 870 to 2200 meters above sea level. Inside the house is the site where T. mexicana was present in a major frecuency, for T. barberi was the yard, for T. longipennis inside the house, as well as the T. pallidipennis and the ninphs, T. dimidiata which was collected once, did not reported collect site.